A New Modification to the Chemical Mass Balance Receptor Model for Volatile Organic Compound Source Apportionment - Demir, Selami; Saral, Arslan (WILEY, 2011)
In this study, a modification to the chemical mass balance (CMB) receptor model presented in an earlier work was expanded to account for the changes in volatile organic compound (VOC) source fingerprints due to atmospheric reactions of VOCs that take place after being emitted to the atmosphere. The photochemical reactions consume VOCs that participate in, causing changes in the source fingerprints. These changes are of considerable magnitude when the travel durations from the source to the receptor (measurement point) are considered. The current study focuses on expansion of the integrated reaction rates of VOCs with ambient reactive species such as OH center dot, O-3, NO3, and O-center dot in order to estimate the source emission profiles simultaneously at the receptor site. Two test cases with different travel times and with different ambient OH center dot, O-3, and NO3 concentrations were also provided to compare the standard model, the modified model suggested in the previous work, and the current modification. F-tests were also performed to determine whether the changes in source compositions are significant or not. The results from both the standard model and the modified model were evaluated in terms of chi(2), R-2, percent mass apportioned (MA), and a best fit (BF) measure. Maximum values of BF for the test cases from the three models were 0.70 +/- 0.03, 0.74 +/- 0.05, and 1.000 +/- 0.00, respectively, indicating that the current modification increases the performance of two previous models and was better in explaining the effects of chemical reactions of VOCs.
Keywords: Air pollution; CMB; Modeling; Source apportionment; VOC; MAXIMUM INCREMENTAL REACTIVITIES; ENVIRONMENTAL CHAMBER; VOCS; Science & Technology - Other Topics; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources